Strategy for improving the quality of education through meeting the standards manpower of education in junior high school - Tina Rosalina; Happy Fitria; Achmad Wahidy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
How much influence is the strategy for improving the quality of education through meeting education standards and education personnel. The purpose of this study is to find and describe efforts to improve education standards and education personnel in schools in terms of: planning, implementing and supervising education, influencing, directing teachers and school staff in improving the quality of education. As stated in the National Education Standards (SNP) article 1 No. 17 of Law 20/2003 on National Education System and article 3 of Government Regulation No. 19 Year 20015 that: